RELATIONSHIP BETWEEN CFBM PATTERN BY MOTHERS AND CHILD GROWTH AGED 6–24 MONTHS - Panca Radono; Kurnia Wira Susanti; Riza Tsalatsatul M; Nurwijayanti (Universitas Karya Husada Semarang, 2025)
Introduction: Nutritional problems are crucial in human life. Malnutrition affects health by increasing morbidity, mortality, and disability while also reducing a country's human resource quality. Objective: This study analyzes the relationship between maternal complementary feeding patterns and child growth among children aged 6 to 24 months in Bago Village. Methods: This research employs an observational analytic method with a cross-sectional approach. A total of 80 respondents were selected using accidental sampling. The independent variable is maternal knowledge about complementary feeding, while the dependent variable is child growth. Data analysis was conducted using the Spearman Rho test to examine the relationship between the two variables. Result: Findings indicate that 43 mothers (53.8%) demonstrated good complementary feeding practices, while 71 children (88.8%) exhibited good growth. The Spearman Rho test yielded a p-value of 0.000 (<0.05), leading to the rejection of H0 and acceptance of H1. This confirms a significant correlation between maternal complementary feeding patterns and child growth. Conclusion: proper complementary feeding is essential for meeting toddlers' nutritional needs. Adequate nutrition supports optimal growth and development, while growth barriers may manifest as weight discrepancies relative to age.